The orchid-bee faunas (Hymenoptera: Apidae) of ‘Reserva Ecológica Michelin’, ‘RPPN Serra Bonita’ and one Atlantic Forest remnant in the state of Bahia, Brazil, with new geographic records - Nemésio,A (2014)
The orchid bee faunas of two private natural preserves, ‘Reserva Particular do Patrimônio Natural da Serra Bonita’ (RSB) and ‘Reserva Ecológica Michelin’ (REM), and a forest fragment inside the campus of the ‘Universidade Estadual de Santa Cruz’, were surveyed for the first time. All three areas constitute Atlantic Forest remnants in the southern portion of the state of Bahia, Brazil. A total of 1,782 males belonging to 32 species were actively collected with insect nets during 90 hours of field work from November, 2009, to January, 2012. Euglossa cyanochlora Moure, 1996—one of the rarest orchid bee species—was found at RSB and REM, the latter representing the northernmost record for this species. Euglossa cognata, Moure, 1970 was found at RSB, the northernmost record for this species in the Atlantic Forest and the only recent record for this species at the northern border of Jequitinhonha river.